2020
DOI: 10.35808/ersj/1706
|View full text |Cite
|
Sign up to set email alerts
|

Succession and Ownership in Family Businesses

Abstract: Purpose: We assess the relationship between a potential change in the ownership structure and the change in the scope of control over managing a family business. Design/Methodology/Approach: Analyzing the data characterizing the 500 largest family businesses, correlations between variables were calculated to observe relationships that primarily affect the size of family shares in the company and family impact on management. Findings: The reduction of family shares is also associated with the loss of participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…This statement also corresponds to research in Taiwanese family businesses (Luan et al 2018). Drewniak et al (2020) claimed, however, that an external successor can increase a family business's sales. When owners prefer their own offspring, according to Kandade et al (2021), their early affiliation to the family business is required.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…This statement also corresponds to research in Taiwanese family businesses (Luan et al 2018). Drewniak et al (2020) claimed, however, that an external successor can increase a family business's sales. When owners prefer their own offspring, according to Kandade et al (2021), their early affiliation to the family business is required.…”
supporting
confidence: 77%
“…In this research, we found that owners prefer sons as successors, and this statement corresponds to Wang (2010), andAhrens et al (2015). In selecting a successor, Drewniak et al (2020) pointed out that the successor should have the charisma and personality of a manager. They do not need to be an ideal copy of the current owner.…”
mentioning
confidence: 66%
“…Consistent with that view, Mowday et al (1979), Porter et al (1974 and Steers (1979) further emphasize that engagement is an employee's willingness to contribute to significant efforts for business. The importance of employee expectations towards leaders and the factors fostering positive relations between employees is emphasized (Drewniak et al 2020;Den Hartog and Belschak 2012). According to Meyer and Allen (1991), commitment to business is a psychological state (desires, needs, and responsibilities) that shows the employee's relationship with the organization and has an impact on the aspirations to stay in the organization.…”
Section: Corporate Brand Equity and Employee's Opportunistic Behaviormentioning
confidence: 99%
“…Measurements of the phenomenon of family member engagement in the functioning of family businesses make contemporary researchers come together to focus on issue and may constitute a new field of studies (Więcek-Janka, 2014). The authors are of the opinion that many entrepreneurs are not aware of the full potential of family engagement and are treating the behaviours taking place in the company as organisational routine (Drewniak, 2020;Charupongsopon and Puriwat, 2017;Hys, 2016). The phenomenon constituted the basis for identifying the research problem covered in the question: what organisational effectiveness factors are specific for the functioning of family businesses?…”
Section: Introductionmentioning
confidence: 99%